Entrepreneurship Training in Schools: Fostering an Entrepreneurial Spirit from an Early Age for an Independent Future - Astuti, Lusia Cipto; Anugrah, Annisa Putri; Sugiarto, Agus; Sulaeman, Sulaeman; Fauzi, Muhammad Sukron; F. Farawowan, Fauziah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Entrepreneurship training at the elementary school level is an important step in fostering an entrepreneurial spirit among the younger generation. This activity aims to provide students with basic knowledge and skills in entrepreneurship, as well as develop creative, innovative, and independent attitudes. The training, conducted at an elementary school in Cirebon City, involved 20 students from grades 5 and 6, with material covering the fundamentals of entrepreneurship, identifying business opportunities, and business planning and management. In addition to theoretical lessons, the activity was also supplemented with practical exercises, such as creating simple business plans and simulating buying and selling transactions, allowing students to directly experience the dynamics of the business world. The results of this activity show that students not only acquired new knowledge but also improved their communication skills, creativity, and critical thinking abilities. This training is expected to motivate students to become resilient young entrepreneurs, ready to face future challenges.